P22 Effect of carnitine supplementation on cardiac function and metabolism assessed using CINE MRI and hyperpolarized MRS. (26th October 2016) - Savic, Dragana; Ball, Vicky; Heather, Lisa C; Tyler, Damian
Abstract : Carnitine is responsible for the movement of fatty acids across the mitochondrial membrane to allow for subsequent β-oxidation. Carnitine has been shown to act as a buffer for excess acetyl units within mitochondria through the generation of acetylcarnitine. It is known that carnitine levels are decreased in multiple diseases, such as diabetes and heart failure, and that carnitine supplementation can have a cardioprotective effect. The purpose of this study was to investigate the effect of L-Carnitine supplementation of cardiac function and metabolism in the healthy rat heart. 8 healthy rats treated for 2 weeks with daily IP injections of either L-Carnitine (3 g/kg/day) or saline (control group) were subjected to CINE-MRI, hyperpolarized MRS and echocardiography. Carnitine treated animals gained less weight compared to controls. Cardiac index was higher for the carnitine treated animals compared to controls and diastolic function analysis by echocardiography showed that the E/E' ratio was lower in the carnitine treated group. Hyperpolarized MRS demonstrated elevated acetylcarnitine levels in the myocardium of L-Carnitine treated animals and blood plasma analysis showed increased levels of carnitine in the treated group after 2 weeks of daily treatment with L-Carnitine. For the first time it has been shown that daily injections of L-Carnitine can alter cardiac metabolism and function in vivo in the healthy rat heart, can increase acetylcarnitine levels in the myocardium and improve diastolic function. On-going work is exploring the effect of carnitine supplementation on the diabetic heart to investigate the mechanisms behind the previously demonstrated cardioprotective effects of carnitine supplementation.